Public theology : Indian concerns, perspectives, and themes - Patrick, Gnana (Fortress Press, 2020)
"This book situates public theology within the genre of political theology. Drawing upon the distinct strands of political theologies identified by Daniel M. Bell, Jr., Gnana Patrick treats public theology as the form of political theology for our contemporary era and takes special care to relate these strands of political theologies to the Indian context, thereby opening up the theological horizon for Indian public theology. Further, Public Theology dwells upon certain prominent features of our contemporary global world and discerns the human need for experiencing transcendence today. Taking faith to be the catalyst for this experience of transcendence, it points to civil society as the interstice through which faith can be imparted to the contemporary world. And, it argues for the relevance of public theology for that work."-- Back cover.